Genetic diversity of three European Veratrum species revealed by Amplified Fragment Length Polymorphism - Szeliga, Magdalena; Ciura, Joanna; Tyrka, Mirosław (Biodiversity: Research and Conservation, 2017)
Chemical and genetic characterization of Veratrum species deposited in European collections is important for genepool preservation and identification of populations with desired metabolic properties. Veratrum album, V. lobelianum and V. nigrum are native to Europe, and in Poland are ranked as rare or threatened. Genetic variation of European Veratrum species was characterized by Amplified Fragment Length Polymorphism (AFLP) markers. The accumulation of jervine as a representative of steroidal alkaloids was measured in seeds. Distribution of 380 markers generated from eight primer combinations was useful for studying genetic relationships among and within species in the Veratrum genus and the most divergent populations were identified. Genetic variation between 12 populations of Veratrum species supports the classification of V. lobelianum as a subspecies of V. album. However, the results need further validation on extended material. A higher genetic diversity (22.3%) was observed between populations of V. nigrum as compared to V. album (14.5%). Contents of jervine allowed for discrimination of the studied Veratrum species and can be used as a potential chemotaxonomic marker. The highest jervine levels were found in V. album. V. nigrum seeds had only trace amounts and no jervine was detected in seeds of V. lobelianum.